2021
DOI: 10.1186/s12915-021-00976-8
|View full text |Cite
|
Sign up to set email alerts
|

Winter is coming: the future of cryopreservation

Abstract: The preservative effects of low temperature on biological materials have been long recognised, and cryopreservation is now widely used in biomedicine, including in organ transplantation, regenerative medicine and drug discovery. The lack of organs for transplantation constitutes a major medical challenge, stemming largely from the inability to preserve donated organs until a suitable recipient is found. Here, we review the latest cryopreservation methods and applications. We describe the main challenges—scalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
66
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 221 publications
(273 reference statements)
2
66
0
4
Order By: Relevance
“…ethylene glycol, glycerol, DMSO, or nonpermeable cryoprotectants, e.g. trehalose, sucrose, and then subjected to ultra-rapid cooling, which prevents ice crystal formation and converts the cell content into a so-called glassy state (Bojic et al 2021;Panis et al 2020;Sharma et al 2017). For many microorganisms, freeze drying and liquid drying are often also successfully applied (Smith and Ryan 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ethylene glycol, glycerol, DMSO, or nonpermeable cryoprotectants, e.g. trehalose, sucrose, and then subjected to ultra-rapid cooling, which prevents ice crystal formation and converts the cell content into a so-called glassy state (Bojic et al 2021;Panis et al 2020;Sharma et al 2017). For many microorganisms, freeze drying and liquid drying are often also successfully applied (Smith and Ryan 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the risk of bacterial or viral cross contaminations, specific guidelines or risk assessments have not been developed yet. Although Schafer et al (1976) already pointed out that LN storage tanks might be a source of laboratory infections, most previous reviews on biobanking cover only general information about biobanks (Coppola et al 2019), laboratory operations (Cicek and Olson 2020), cryopreservation procedures (Bojic et al 2021), or specific topics such as global health (Mendy et al 2018) and reproduction medicine (Tao et al 2020). So far, the potential of contamination in cryobanking was only discussed by Larman et al (2014), Bielanski and Vajta (2009), Joaquim et al (2017), andVajta et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, cryoprotectant-free vitrification methods have been attempted in human spermatozoa [ 3 ] and equine oocytes [ 4 ] without success, and so far, it has never been performed in porcine. Moreover, results from previous studies demonstrated the need for CPAs [ 3 6 ], and recently new nontoxic CPAs has been proposed [ 7 ]. For oocyte cryopreservation, ethylene glycol (EG) and dimethylsulfoxide (DMSO) have been the most widely used permeable CPAs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the last century, cryopreservation has been widely used to preserve cells and tissue, and by reducing their decay under extremely cold conditions, keep them alive while maintaining their natural properties. With the discovery of cryoprotective agents, this technique has successfully been used to preserve single cells, but its success rate tends to decrease if used for more complex tissues (Bojic et al, 2021;Karlsson and Toner, 1996).…”
Section: Introductionmentioning
confidence: 99%